Distress of Routine Activities and Perceived Safety Associated with Post-Traumatic Stress, Depression, and Alcohol Use: 2002 Washington, DC, Sniper Attacks. (5th June 2015) - Fullerton, Carol S.; Herberman Mash, Holly B.; Benevides, K. Nikki; Morganstein, Joshua C.; Ursano, Robert J.
Abstract: Objective: For over 3 weeks in October 2002, a series of sniper attacks in the Washington, DC, area left 10 people dead and 3 wounded. This study examined the relationship of distress associated with routine activities and perceived safety to psychological and behavioral responses. Methods: Participants were 1238 residents of the Washington, DC, metropolitan area (aged 18 to 90 years, mean=41.7 years) who completed an Internet survey including the Impact of Event Scale-Revised, Patient Health Questionnaire-9, and items pertaining to distress related to routine activities, perceived safety, and alcohol use. Data were collected at one time point approximately 3 weeks after the first sniper shooting and before apprehension of the suspects. Relationships of distress and perceived safety to post-traumatic stress, depressive symptoms, and increased alcohol use were examined by using linear and logistic regression analyses. Results: Approximately 8% of the participants met the symptom criteria for probable post-traumatic stress disorder, 22% reported mild to severe depression, and 4% reported increased alcohol use during the attacks. Distress related to routine activities and perceived safety were associated with increased post-traumatic stress and depressive symptoms and alcohol use. Conclusion: Distress and perceived safety are associated with specific routine activities and both contribute to psychological and behavioral responses during a terrorist attack. These findings have implications for targeted information dissemination and risk communication by community leaders. ( Disaster Med Public Health Preparedness . 2015;9:509–515)